1980
DOI: 10.1002/ana.410080512
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal (circannual) periodicity of spontaneous intracerebral hemorrhage in minnesota

Abstract: Seasonal periodicity in the onset of spontaneous intracerebral hemorrhage was studied in 118 consecutive cases occurring during a six-year span. The patients were urban residents of eastern Minnesota, a region characterized by wide seasonal fluctuations in daylight and temperature. The greatest number of cases consistently occurred each year during January and February. Circannual (about one year) periodicity was demonstrated by statistical analysis using rhythmometric techniques. This periodicity coincided wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
2
2

Year Published

1983
1983
2001
2001

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(30 citation statements)
references
References 9 publications
3
23
2
2
Order By: Relevance
“…4 Also, in the present study, the January-March incidence (62 cases) was lower than the October-December incidence (75 cases), although the mean ambient temperature was lower in winter (3.73°C) than in autumn (7.63°C). Finally, studies conducted in the Boston and Chicago areas, 7 in the Lehigh Valley, 8 and in the Dijon area 9 did not confirm the seasonal variation of cerebral hemorrhage incidence.…”
Section: »-O >H Time (2-month Penods)contrasting
confidence: 58%
“…4 Also, in the present study, the January-March incidence (62 cases) was lower than the October-December incidence (75 cases), although the mean ambient temperature was lower in winter (3.73°C) than in autumn (7.63°C). Finally, studies conducted in the Boston and Chicago areas, 7 in the Lehigh Valley, 8 and in the Dijon area 9 did not confirm the seasonal variation of cerebral hemorrhage incidence.…”
Section: »-O >H Time (2-month Penods)contrasting
confidence: 58%
“…The number of patients varied widely, and not all series were large enough to have the statistical power for reliable conclusions. 1,5,[11][12][13][14]16,[31][32][33][34][35][36] The diagnosis of ICH was confirmed by imaging studies or autopsy in a few studies, 2,6,13,15,32,33,37,38 and it is often unclear whether ICH was spontaneous or primary. 3-5,8 -12,14 -16,31-34,39,40 In some studies, cases were identified on the basis of International Classification of Diseases (ICD) discharge codes, 8,9,10,39 whereas others included subarachnoid hemorrhage (SAH) 32 or excluded elderly patients.…”
Section: Discussionmentioning
confidence: 99%
“…3-5,8 -12,14 -16,31-34,39,40 In some studies, cases were identified on the basis of International Classification of Diseases (ICD) discharge codes, 8,9,10,39 whereas others included subarachnoid hemorrhage (SAH) 32 or excluded elderly patients. 13 Among studies on the seasonal distribution of ICH, some found increased occurrence of ICH [1][2][3][4][5][6][7][8][9][10]13 in winter, whereas others indicated peaks in other seasons 11,14,37 or no significant seasonal variation at all. 16,[31][32][33][34][35]38,39 However, the most consistent seasonal variation described was a seasonal pattern with a peak of incidence in winter and a minimum in summer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 We did not find a seasonal periodicity in the occurrence of ICH or SAH. The study of patients in climates less severe than Minnesota 24 or Iowa 28 may have minimized seasonal effects on the incidence of intracranial hemorrhage.…”
Section: Discussionmentioning
confidence: 99%